Epidemiology of Demyelinating Diseases in Korean Pediatric Patients. (February 2021) - Yoon, Hye Hyun; Park, Ji Young; Kim, Su Yeong; Lee, Na Mi; Yi, Dae Yong; Yun, Sin Weon; Lim, In Seok; Chae, Soo Ahn
The epidemiology of demyelinating diseases in the Korean pediatric population has not been reported to date. This study aimed to identify the epidemiology of demyelinating diseases in Korean children by using big data. The subjects were children (0-17 years old) diagnosed with acute-disseminated encephalomyelitis, multiple sclerosis, neuromyelitis optica, and Guillain-Barré syndrome enrolled in the Korean Health Insurance Review and Assessment Service (HIRA) from January 2010 to December 2017. Of 1722 enrolled children, 553 (32.1%) had acute-disseminated encephalomyelitis, 170 (9.9%) had multiple sclerosis, 68 (3.9%) had neuromyelitis optica, and 931 (54.1%) had Guillain-Barré syndrome. The male-female ratios were 1.47:1 in acute-disseminated encephalomyelitis, 1.43:1 in Guillain-Barré syndrome, 1:1.66 in multiple sclerosis, and 1:1.62 in neuromyelitis optica. Demyelinating diseases were most prevalent in summer. The prevalence differed by region, with 545 (31.6%) in Seoul and 298 (17.3%) in Gyeonggi. This study is the first to identify the incidence of demyelinating diseases in South Korea.